Polarized Entry of Human Parechoviruses in the Airway Epithelium - Karelehto, Eveliina; Cristella, Cosimo; Yu, Xiao; Sridhar, Adithya; Hulsdouw, Rens; de Haan, Karen; van Eijk, Hetty; Koekkoek, Sylvie; Pajkrt, Dasja; de Jong, Menno D.; Wolthers, Katja C. (Frontiers in Cellular and Infection Microbiology, 2018)
Human parechoviruses (HPeVs), a poorly studied genus within the Picornaviridae family, are classified into 19 genotypes of which HPeV1 and HPeV3 are the most often detected. HPeV1 VP1 C terminus contains an arginine-glycine-aspartic acid (RGD) motif and has been shown to depend on the host cell surface αV integrins (αV ITGs) and heparan sulfate (HS) for entry. HPeV3 lacks this motif and the receptors remain unknown. HPeVs can be detected in patient nasopharyngeal and stool samples, and infection is presumed to occur after respiratory or gastro-intestinal transmission. HPeV pathogenesis is poorly understood as there are no animal models and previous studies have been conducted in immortalized monolayer cell cultures which do not adequately represent the characteristics of human tissues. To bridge this gap, we determined the polarity of infection, replication kinetics, and cell tropism of HPeV1 and HPeV3 in the well-differentiated human airway epithelial (HAE) model. We found the HAE cultures to be permissive for HPeVs. Both HPeV genotypes infected the HAE preferentially from the basolateral surface while the progeny virus was shed toward the apical side. Confocal microscopy revealed the target cell type to be the p63+ basal cells for both viruses, αV ITG and HS blocking had no effect on the replication of either virus, and transcriptional profiling suggested that HPeV3 infection induced stronger immune activation than HPeV1. Genotype-specific host responses may contribute to the differences in pathogenesis and clinical outcomes associated with HPeV1 and HPeV3.